The Degree of Awareness of Certified Trainers in the Kingdom of Saudi Arabia about the Importance of Certified Trainer’s License the degree to which they benefit from it - Al-Qahtani, Kholoud Mohammed Naïf Al-Suheimy; Al-Qahtani, Remsh Nasser Saad (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the degree of awareness of trainers about the importance of license and the degree to which they benefit from it. It used the descriptive approach, and a questionnaire was built, it was distributed to all the study population (trainers who have a certified trainer license in the Kingdom), the number of sample was (330). The results showed that the degree of awareness of the trainers is very high, but the degree of the benefit of it is high. There were no differences in the degree of awareness of the trainers by (type, region, qualification, training experience), there were no differences about the degree to which they benefit from it by (region, training experience), but there were differences by (type, qualification).